An Efficient Access to Aspermytin A and Oblongolide C through an Intramolecular Nitrile Oxide–Alkene [3+2] Cycloaddition - Inoue, Atsushi; Kanematsu, Makoto; Mori, Seiji; Yoshida, Masahiro; Shishido, Kozo (Synlett, 2013)
The second generation synthesis of (+)-aspermytin A and the first total synthesis of (–)-oblongolide C have been accomplished employing an intramolecular nitrile oxide–alkene [3+2] cycloaddition as the key step.
Keywords: total synthesis; enantioselectivity; cycloaddition; aspermytin A; nitrile oxide